To what extent is antenatal care in public health facilities associated with delivery in public health facilities? Findings from a cross-section of women who had facility deliveries in Nigeria - Benjamin Bukky Ilesanmi; Bola Lukman Solanke; Tosin Olajide Oni; Rasheed Adebayo Yinusa; Omolayo Bukola Oluwatope; Olaoye James Oyeleye (BMC, 2023)
Abstract Background Facility delivery remains an important public health issue in Nigeria. Studies have confirmed that antenatal care may improve the uptake of facility delivery. However, information is rarely available in Nigeria on the extent to which antenatal care in public health facilities is associated with delivery in public health facilities. The objective of the study was thus to examine the extent of the association between antenatal care in public health facilities and delivery in public health facilities in Nigeria. The study was guided by the Andersen behavioral model of health services use. Methods The cross-sectional design was adopted. Data were extracted from the most recent Nigeria Demographic and Health Survey (NDHS). A sample of 9,015 women was analyzed. The outcome variable was the facility for delivery. The main explanatory variable was the antenatal care facility. The predisposing factors were maternal age, age at first birth, parity, exposure to mass media, and, religion. The enabling factors were household wealth, work status, partners' education, women's autonomy, health insurance, and, perception of distance to the health facility. The need factors were pregnancy wantedness, the number of antenatal care visits, and the timing of the first antenatal care. Statistical analyses were performed with the aid of Stata version 14. Two binary logistic regression models were fitted. Results Findings showed that 69.6% of the women received antenatal care in public health facilities, while 91.6% of them subsequently utilized public health facilities for deliveries. The significant predisposing factors were age at first birth, parity, maternal education, and religion, while household wealth, work status, women's autonomy, and partners' education were the significant enabling factors. The timing of the first antenatal contact, pregnancy wantedness, and the number of antenatal care visits were the important need factors. Conclusion To a significant extent, antenatal care in public health facilities is associated with deliveries in public health facilities in Nigeria. It is imperative for governments in the country to take more steps to ensure the expanded availability of public health facilities in all parts of the country since their use for antenatal care is well-associated with their use for delivery care.